Does metabolic rate increase linearly with running speed in all distance runners? - Batliner, M. E.; Kipp, S.; Grabowski, A. M.; Kram, R.; Byrnes, W. C. (Sports Medicine International Open, 2018)
Running economy (oxygen uptake or metabolic rate for running at a submaximal speed) is one of the key determinants of distance running performance. Previous studies reported linear relationships between oxygen uptake or metabolic rate and speed, and an invariant cost of transport across speed. We quantified oxygen uptake, metabolic rate, and cost of transport in 10 average and 10 sub-elite runners. We increased treadmill speed by 0.45 m·s-1 from 1.78 m·s-1 (day 1) and 2.01 m·s-1 (day 2) during each subsequent 4-min stage until reaching a speed that elicited a rating of perceived exertion of 15. Average runners` oxygen uptake and metabolic rate vs. speed relationships were best described by linear fits. In contrast, the sub-elite runners` relationships were best described by increasing curvilinear fits. For the sub-elites, oxygen cost of transport and energy cost of transport increased by 12.8% and 9.6%, respectively, from 3.58 to 5.14 m·s-1. Our results indicate that it is not possible to accurately predict metabolic rates at race pace for sub-elite competitive runners from data collected at moderate submaximal running speeds (2.68-3.58 m·s-1). To do so, metabolic rate should be measured at speeds that approach competitive race pace and curvilinear fits should be used for extrapolation to race pace.